Creative Economy Dynamics in the Era of Algorithmic Culture: Indonesia's Content Creator Strategy in Monetizing Content on TikTok and YouTube Shorts Platforms (Behavioral Economics Approach) - Fauziyyah, Ghina (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
The development of Indonesia's digital creative economy is increasingly influenced by algorithmic culture, where platforms such as TikTok and YouTube Shorts dictate the visibility and monetization of content. Content creators are required to constantly adapt to the uncertain logic of platforms, creating unique and complex economic dynamics. This research aims to: (1) Map the monetization strategy of Indonesian content creators on the TikTok and YouTube Shorts platforms; (2) Analyze the influence of algorithmic culture on their economic decision-making; and (3) Explain the strategy through a behavioral economics approach. The research used the mixed-methods method sequentially (explanatory sequential). Qualitative data was collected through in-depth interviews with 20 content creators and content analysis. Quantitative data was obtained through a survey of 200 respondents to test the qualitative findings. Research reveals that creators adopt highly diversified monetization strategies to overcome algorithmic uncertainty. High levels of algorithmic literacy correlate with more consistent income. Key findings suggest that economic decision makers are heavily influenced by cognitive biases such as present bias (prioritizing instant rewards) and optimism bias (excessive expectations of viral success). In conclusion, a monetization strategy is a form of behavioral adaptation to algorithmic pressures. The implications of the findings highlight the need for improved algorithm literacy and policy support to create a more sustainable and less platform-dependent creative economy ecosystem, as well as the importance of behavioural economics approaches in understanding the platform economy.